Electronic Media and Early Childhood: A Review - Paulus, Frank W.; Möhler, Eva; Recktenwald, Franziska; Albert, Amélie; Mall, Volker (Klinische Pädiatrie, 2021)
Background This review summarizes the state of knowledge of use of new media on the development in early childhood in 6 sections: descriptive utilization data, psychosocial and emotional development, cognition and language, motor development, nutrition and sleep, and influence of parental media consumption.Methods The review is based on a literature search of this topic in peer-reviewed journals. We included 87 articles, books, and book chapters. The used literature data bases were ERIC, PsycARTICLES, PsycINFO and PSYNDEX.Results Manifold studies describe in young children’s utilization data the pervasive nature of digital exposure and impressive usage times and availability. They confirm adverse influences of electronic media use (television, video games) on children’s emotional and behavioral problems and well-being, e. g. on physical activity, sleep and obesity. In general a positive effect in sense of knowledge transfer of age could be found for high quality educational media, however predominantly the impact of media use at younger age was negative.Conclusions High frequent media use in early childhood is likely to have a negative impact on psychosocial development, positive effects such as knowledge transfer may be seen beyond the age of 18 months. As parental media use is a strong predictor of child media habits, reducing parental media use and enhancing parent–child interactions might be important areas to address when trying to change the media behavior of young children. In view of the scarcity of studies for early childhood, it is advisable to use digital play and communication devices cautiously and restrictively in this vulnerable development phase.
Keywords: electronic media; digital; infant; toddler; development; parental media use